Meningkatkan Kemampuan Pemecahan Masalah Melalui Pendekatan Kontekstual Pada Siswa Kelas VIII di Kabupaten Bandung Barat - Yani Komalasari; Resti Naila N.T; Neni Maryani; Fitriani Nursalamah; Nani Marlina; Wahyu Hidayat (Mathematics Education Study Program, 2019)
The purpose of this study is to examine the achievement of problem solving abilities of junior high school students using contextual and teaching leaning learning. The study population included all seventh grade students of SMP in West Bandung Regency. From the population that was taken randomly, namely class VII I amounted to 44 students using a leaning contextual and teaching approach and class VII J amounted to 44 students with classes using conventional learning. The data collection used is a test question in the form of a test of problem solving ability totaling five questions with indicators (1) understanding the problem (2) planning completion (3) completion according to plan (4) checking again. To test the effectiveness of learning by using a leaning contextual and teaching approach and conventional tests used inality tests. To compare the average achievement of contextual learning and leaning teaching and conventional learning the data were analyzed using the two sample t-test. The results of this study indicate that the overall achievement of problem-solving skills is seen that there are differences using contextual learning and leaning teaching rather than conventional learning.